Papan Semen Partikel Campuran Kayu Jabon (Anthocephalus Cadamba Miq.) dan Sekam Padi Berdasarkan Variasi Tekanan Kempa - Irvin Dayadi (Jurnal Multidisiplin Madani, 2022)
This research aims to determine the quality of cement-bonded particleboard based on variations in pressure from a mixture of jabon (Anthocephalus cadamba Miq.) and rice husks with a ratio of 50:50 at board density target of 1 g/cm3. The pressure variation was 20, 25, and 30 bar for 4 hours, while the catalyst used was Ca(OH)2. Physical and mechanical properties testing including density, moisture content, water absorption, thickness swelling, MoE, MoR and IBS tests referring to International Standards ISO 8335: 1987 and British Standards BS 5669: 1989. The test results show better quality trends at higher pressures and have met both standards on the physical properties, whereas mechanical properties does not meet both standards.